Pathways to Attaining a Food Secure Philippines through a Competitive and Climate-Resilient Agri-Fisheries Sector - Vidallo, Rene R.; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Monville-Oro, Emilita; Gonsalves, Julian Francis; Ilaga, Alicia; Sebastian, Leocadio S.; Manalo, U-Nichols; Baltazar, Perla (International Institute for Rural Reconstruction, 2019)
This document highlights the key messages drawn from climate adaptation efforts and events done with Philippines’ Department of Agriculture-Regional Field Offices (DA-RFOs) across the country. This brief, developed for the Climate Change Consciousness Week, offers DA a synthesis of lessons from the Adaptation and Mitigation Initiative in Agriculture (AMIA) village experience as a bankable model for establishing context specific, local adaptation platforms for developing and disseminating CRA technologies and processes. This brief also offers valuable policy insights for the Philippines’ National Adaptation Plan.